U-shaped impacts of institutional quality and ICT penetration on economic growth: Evidence from selected emerging countries - Thanh Phuc Nguyen; Dinh Thi Thu Hong; Ngoc Tho Tran; Trang Duong Thi Thuy (Cogent Economics & Finance, 2022)
This research aims to consider determinants of economic growth, such as financial development, institutional quality, and information and communication technology (ICT) penetration, which have been explored separately in previous studies and have produced mixed findings in different regions. Using the two-step system generalized method of moments (GMM) estimator for a dynamic panel dataset of 35 selected emerging countries, several research findings could be drawn as the following. First, both ICT penetration and institutional quality have significantly positive effects on economic growth. On the contrary, economic development could be hampered by financial development. Second, there are the U-shape and inverted U-shape relations for the cases of institutional quality and ICT penetration on economic growth, respectively. Third, the interaction effect of ICT penetration and financial development could enhance economic growth while the negative impact of financial development on economic development is amplified by the high level of institutional quality. These findings are robust to the global financial crisis control and the use of an alternative ICT proxy when setting up the approach of principal component analysis. Given these findings from emerging countries, some policy challenges that policy-makers should address by simultaneously considering each growth driver, such as financial development, ICT evolution, and institutional quality and interactions between them, as well as the non-monotonic effect of ICT penetration and institutional quality to facilitate economic growth.
Keywords: 330; Economic growth; emerging countries; financial development; ICT penetration; institutional quality